Tariffs and the Balance of Payments - Ozga, S. A. (Quarterly Journal of Economics, 1957)
Journal Article Tariffs and the Balance of Payments Get access S. A. Ozga S. A. Ozga London School of Economics and Political Science Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 71, Issue 4, August 1957, Pages 630–638, https://doi.org/10.2307/1885714 Published: 01 August 1957